Efektivitas aplikasi kompos kulit kopi dan Fungi mikoriza arbuskular terhadap produktivitas jagung manis - Hary Sahputra; Suswati Suswati; Gusmeizal Gusmeizal (Universitas Medan Area, 2019)
Corn is one of stupple food to support economic growth in North Sumatera. The purpose of this research was to obtain data on the ability of compost derived from coffee husks and arbuscular mycorrhizal fungi in the growth and production of sweet corn plants (Zea mays sccharata Sturt). The method used in this study is a randomized block design (RDB) in factorial, with 2 (two) treatment factors, namely: 1) Factor coffee skin and Â 2) arbuscular mycorrhizal fungi (M), each treatment was repeated two (2) times so that there are 40 experimental plots. The parameters observed are plant height, number of leaves, cob length, sample crop production per plot, crop production per plot, top wet weight, bottom wet weight, percentage of pest attack, colonization of arbuscular mycorrhizal fungi, effectiveness of treatment application to all parameters. The results obtained from this study were: 1) The giving of coffee skin compost did not significantly affect the parameters of plant height, number of leaves, cob length, sample plant production per plot, crop production per plot, top wet weight and bottom wet weight; 2) The allocation of arbuscular mycorrhizal fungi has no significant effect on the parameters of observing plant height, number of leaves, cob length, sample plant production per plot, crop production per plot, top wet weight and bottom wet weight; 3) The combination of coffee husks compost and arbuscular mycorrhizal fungi did not significantly affect the parameters of plant height, number of leaves, length of cob, sample crop production per plot, crop production per plot, top wet weight and bottom wet weight.